2021
DOI: 10.1186/s12879-021-05869-3
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis in a tertiary unit in South Africa

Abstract: Background Antimicrobial resistance (AMR) has emerged as a global threat to healthcare resulting in an increase in morbidity and mortality. Neonatal sepsis is ranked as the third highest cause of neonatal demise globally, in which AMR accounted for 31.0% of deaths. AMR in neonates has been poorly characterised in Durban, South Africa. Thus, the resultant effect of AMR on empiric regimens for neonatal sepsis is uncertain in this setting. Therefore, this study analysed the aetiology and antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 33 publications
7
37
1
Order By: Relevance
“…In our study, MRSA among S. aureus isolates was 79% (11/14) which was a high propotion as also reported in orther studies [48], which could have been due to transmission from the colonized maternal genital tract or from the labour ward after unhygienic obstetric practices. However this was relatively higher than what was reported by Eyob (72%), the difference could have been due to geographical differences ie variation in the frequency of the organisms within and between coutries, types of the specimen, laboratory procedures, study population, and study duration and differences in study design [49].…”
Section: S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%)supporting
confidence: 82%
“…In our study, MRSA among S. aureus isolates was 79% (11/14) which was a high propotion as also reported in orther studies [48], which could have been due to transmission from the colonized maternal genital tract or from the labour ward after unhygienic obstetric practices. However this was relatively higher than what was reported by Eyob (72%), the difference could have been due to geographical differences ie variation in the frequency of the organisms within and between coutries, types of the specimen, laboratory procedures, study population, and study duration and differences in study design [49].…”
Section: S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%) S (%) R (%)supporting
confidence: 82%
“…is elsewhere reported to be one of the dominant species in neonatal sepsis in LMICs. 1 , 72 , 74 Pillay et al in 2021 (South Africa), reported K. pneumoniae within the three leading causes of EOS, with coagulase-negative staphylococcus (CoNS) and A. baumannii . 74 Two years previously however, Velaphi et al (South Africa) in 2019 published data to the contrary revealing GBS and Ureaplasma spp.…”
Section: Bacterial Diversity Of Eos In Africamentioning
confidence: 99%
“…Due to ease of access and simplicity to determine levels of AMR and classify the bacterial isolate as either sensitive (S) or resistant (R), many hospital laboratories use disc diffusion assays, 70 , 88 , 89 or E-tests. 66 , 90 Facilities with better resources in, other studies report minimum inhibitory concentration data interpreted from automated systems such as the VITEK, 74 or via agar dilution. 1 , 3 Moreover, different studies follow different reporting guidelines with both CLSI and EUCAST commonly used, amongst others, making data comparison difficult.…”
Section: Antimicrobial Resistance In Neonatal Sepsis: a Summarymentioning
confidence: 99%
“…An upsurge in ESBL-producing K. pneumoniae sepsis has been observed over the world, with the NICU accounting for the majority of cases. 31 Antimicrobial resistance in Klebsiella is mostly linked with the formation of ESBL. In 2017, the WHO included ESBL-producing Klebsiella as most dangerous superbugs along with Pseudomonas aeruginosa and Acinetobacter baumanni.…”
Section: Discussionmentioning
confidence: 99%